Cultural Border Crossing: An Exploration of Power, Positionality, and Pedagogy in Context - Kathryn Nielson-Dube; Diane McEachern (Adult Education Research Conference, 2010)
This paper explores literature drawn from interdisciplinary scholarship that speaks to positionality as it applies to the complex dynamics of intercultural border crossing through the lens of two distinctly different institutional contexts – an adult service learning partnership at a private, Northeastern college and an indigenous adult cohort university program.